Estabilishing Plant Production Systems by Optimising the Crop Structure - Sulyok, Zsolt Dénes (Acta Agraria Debreceniensis, 2003)
In our days, ecologiacal and economic models of agricultural application are of ever increasing significance. These provide an opportunity for more accurate planning, and thus can favourably influence the efficiency and the economic situation of the given enterprise. The relevant literature divides models according to various criteria. The most common is the division between optimising and non-optimising models. Non-olptimising models generally endeavour to make the best use of technological lines, of machine capacity, while optimising models are used to optimise revenues returns from sales; or occasionally, production costs. In our case revenue and returns from sales were optimised. The models examined consists of several modules. These are the following: plant cultivation modules, evaluations (assessment of situation, conception plan, complex corporate evaluation), supplementary sheets (sheets and charts for ancillary plant production, general costs of operation, summary and crops structure optimisation). With the help of the model annual plans of plant cultivation can be made an optimal crop structure may be planned with the resources of the enterprise taken into consideration, and thereby it becomes possible to define the largest net revenue on a corporate level.